A role for microtubules in sorting endocytic vesicles in rat hepatocytes. - Goltz, J S (1992)
The vectorial nature of hepatocyte receptor-mediated endocytosis (RME) and its susceptibility to cytoskeletal disruptors has suggested that a polarized network of microtubules plays a vital role in directed movement during sorting. Using as markers a well-known ligand, asialoorosomucoid, and its receptor, we have isolated endocytic vesicles that bind directly to and interact with stabilized endogenous hepatocyte microtubules at specific times during a synchronous, experimentally initiated, single wave of RME. Both ligand- and receptor-containing vesicles copelleted with microtubules in the absence of ATP but did not pellet under similar conditions when microtubules were not polymerized. When 5 mM ATP was added to preparations of microtubule-bound vesicles, ligand-containing vesicles were released into the supernatant, while receptor-containing vesicles remained immobilized on the microtubules. Release of ligand-containing vesicles from microtubules was prevented by monensin treatment during the endocytic wave. Several proteins, including the microtubule motor protein cytoplasmic dynein, were present in these preparations and were released from microtubule pellets by ATP addition concomitantly with ligand. These results suggest that receptor domains within the endosome can be immobilized by attachment to microtubules so that, following monensin-sensitive dissociation of ligand from receptor, ligand-containing vesicles can be pulled along microtubules away from the receptor domains by a motor molecule, such as cytoplasmic dynein, thereby delineating sorting.